A systematic review of reproductive physiology of jaguars (Panthera onca) - Ortiz, Gala (2022)
The jaguar (Panthera onca), the largest felid in the Americas, has been classified by IUCN as „near-threatened‟. The purpose of this review was to gather the current knowledge on jaguar reproduction. Information from over forty-five sources has been selected. Jaguars have been classified as polyestrous with generally an inducedovulation, with a moderate incidence of spontaneity. Estrus, estrous cycle and pseudopregnancy lengths varied from 4 to 17, and 22 to 63, and 14 to 67 days, respectively. Ejaculate volume is around 3.9 ml and the spermatogenic cycle takes 57.7 ± 0.07 days. In spite of its low gonadosomatic index, the whole spermatogenic process in jaguars is more efficient than that of the domestic cat. Although minor seasonal variation in most reproductive traits has been found at the studied latitudes, local rains seemed to have an effect. Gestation takes from 91 to 111 days. Females queen one to four immature cubs. As evidenced by the wide range reported for most reproductive parameters further work is still necessary to achieve fundamental knowledge that could facilitate breeding, management and conservation activities.